FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN BAYI BERAT LAHIR RENDAH (BBLR) DI RSUD HASSANUDIN DAMRAH BENGKULU SELATAN - Ruri Mayseptia Sari; Buyung Keraman; Enita Apriliani (Jurnal Sains Kesehatan, 2017)
The purpose of this study was to determine Factors associated with Incidence of Low Baby Weight (Preeclampsia, Anemia, Dinstance of Pregnancy) at HasanuddinDamrah Hospital South Bengkulu. This study was survey analytic used case control design. Population in this study was all baby was born from mothers who were multigravida at Hasanuddin Damrah Hospital South Bengkulu 2015 with amount 0f 465 infants. Sample in this study divided by two grouf that was case grouf with the amount of 88 infants obtained with total sampling and control group with the amount of 88 infants obtained with systematic random sampling. Data analysis in this study Chi-Square, to determine closed relationship used contingency coefficient (C), while to determine risk factor used Odd Ratio (OR). The result of the study showed: (1) there were 88 infants (50%) with low Baby Weigh, (2) there was relationship between preeclampsia with Incidence of Low Baby Weigh (3) mother with preeclampsia had risk delivered with Low Baby Weigh 5,012 times compared with mother did no preeclampsia, (4) there was relationship between anaemia with Incidence of Low Baby Weigh, (5) mother with anaemia had risk delivered with Low Baby Weigh 2,778 times compared with mother did not anaemia, (6) there was relationship between distance of pregnancy with Incidence of Low Baby Weigh, (7) mother with distance of pregnancy 2 years had risk delivered with Low Baby Weigh 6,663 times compared with mother with distance of pregnancy ≥2 years.Keywords: anemia, baby, distance of pregnancy, low birth weight, preeclampsia,